Genome-wide identification of CDPKs in jujube and expression profile analysis in response to multiple biological processes - Lili Li; Ye Yuan; Bingqi Shen; Chong Chen; Lei Yang; Juan Jin; Dingyu Fan; Qing Hao (Frontiers in Plant Science)
As calcium responders, calcium dependent protein kinases (CDPKs) play an important role in plant growth and development and in response to biotic and abiotic stresses. However, information on CDPKs in jujube (Ziziphus jujuba Mill.) (ZjCDPKs) is limited. In the current study, a total of 21 ZjCDPKs were identified, which are located on eight chromosomes. Gene structure and conserved motif analysis showed that all ZjCDPKs have similar gene structures and conserved motifs, except for ZjCDPK9 and ZjCDPK21. The CDPKs from Arabidopsis, rice, tomato, alfalfa, and jujube were divided into eight subgroups, and the members of ZjCDPKs were unevenly distributed across these subgroups. Colinear analysis revealed that 12 homozygous CDPKs were detected between jujube and Arabidopsis, and 14 pairs were found between jujube and tomato. Additionally, four types of cis-acting elements were identified in the promoters of the ZjCDPKs, including hormone, stress, development, and light response elements. The expression profiles of ZjCDPKs at different fruit growth stages, in response to phytoplasma infection, cold, and salt stresses revealed that most ZjCDPKs were either up- or down-regulated. Finally, varying numbers of transcription factors were observed to interact with the promoter region of ZjCDPK4/6/7/8/10/14/16 and showed opposite expression patterns in response to cold or salt stress. The systematic analysis of ZjCDPKs provides important information for further functional characterization of CDPKs in jujube in response to multiple biological processes.